MEMBANGUN RELATIONSHIP QUALITY UNTUK MENINGKATKAN BRAND IMAGE,RELATIONSHIP VALUE, DAN PARTICIPATION INTENTION PRODUK ICONNET - Astuti, Puji; Dwikaryana, Farhan; Rojuaniah, Rojuaniah; Hazrati Havidz, Ikramina Larasati; Sansetika, Lutfi Eka (JURNAL ILMIAH EDUNOMIKA, 2024)
The marketing strategy involving consumers is currently a dissolution which is considered effective with product promotions carried out by the companies themselves (Strand & Robertson, 2020). Relationship quality is a key factor in marketing strategies that involve consumers, because it will illustrate how strong the relationship between brands and consumers is (Adhikari & Panda, 2020). According to Shahid et al. (2023) good relationship quality allows consumers not only to understand a brand better, but will enable consumers to participate in spreading good things about the brand. The purpose of this study was to examine the relationship between social media marketing activities and customer experience as a preliminary to relationship quality, and how the quality of the relationship between a customer and a brand impacts brand image, intention to participate, and relationship value. This study uses a quantitative approach where data collection is carried out through surveys by distributing online questionnaires via Google Forms which are posted directly to ICONNET customers. Based on the test results of this study, it is proven that there is a relationship between some of the variables, although some do not affect one another. Based on the results that can be concluded in this study, social media marketing activities & customer experience are not the driving factors for relationship quality. However, this study was successful in confirming the influence of brand image, participation intention, and relationship value on the quality of Iconnet's customer relationships.